Intrinsic hysteresis loops in ferroelectric film systems - Chew, Khian Hooi; Tilley, D.R.; Ong, L.H.; Osman, J.; Tan, E.K. (2001)
With the increasing emphasis on the applications of ferroelectric films in memory devices, it is relevant to calculate hysteresis loops for film systems. Here we present two calculations based on the Landau-Devonshire free energy. First we deal with a ferroelectric bilayer with an assumed antiferroelectric coupling across the interface. The calculations apply equally to a superlattice with this coupling. We show that by variation of the ratio L-1/L-2 of the film thicknesses it is possible to engineer the hysteresis loop between a form similar to that of a bulk antiferroelectric for L-1/ L(2)approximate to1 and a ferroelectric form for L-1/L-2 >>1. The bilayer model includes the simplifying assumption that the polarization is constant in each film. We go on to discuss inclusion in the hysteresis calculations of polarization variation P(z) within a film; for simplicity we deal with a single film. We show that the numerical scheme used for first-order films (Ong et al., these Proceedings) can be extended to include an applied field so that hysteresis loops can be calculated; some examples are given.